Religious Moderation as a Negotiation Process: Implementation of the Policy on the Right to Learn Islamic Religious Education for Muslim Students - Sanusi Sanusi; Ihsan Ihsan (Newinera Publisher, 2026)
This study examines the implementation and negotiation process of the Islamic Religious Education (ISE) right-to-learn policy in Christian-based schools with a majority of Muslim students, through a case study of SMK Kristen Nusantara Kudus. Religious moderation is understood as a dynamic social process, shaped through the interaction of daily practices, symbolic constructions, and power relations within the school environment. The study used a qualitative approach with a case study design through in-depth interviews, observations, and document analysis with the principal, Islamic Religious Education (ISE) teachers, and Muslim students. The results show that the implementation of Islamic Religious Education (ISE) not only represents administrative compliance with regulations but also serves as an institutional strategy for managing diversity while maintaining institutional identity. Interview data revealed that formally the school has fulfilled institutional justice by providing Muslim teachers, worship facilities, and learning arrangements. However, at the practical level, all participants revealed that at the beginning of each lesson, and in every formal activity such as prayer ceremonies, there are two prayers, one in Islamic and one in Christian, indicating the existence of symbolic and emotional boundaries in social interactions. Islamic Religious Education (ISE) teachers also negotiate pedagogical practices of caution in delivering material, by avoiding sensitive and potentially conflict-inducing material. This includes students' self-discipline during Christian prayer, as well as their feelings of gradually becoming accustomed to the presence of symbols of Christian identity.